Adenylyl cyclase isoforms 5 and 6 in the cardiovascular system: complex regulation and divergent roles - Maghsoudi, Saeid; Shuaib, Rabia; Van Bastelaere, Ben; Dakshinamurti, Shyamala (Frontiers in Pharmacology, 2024)
Adenylyl cyclases (ACs) are crucial effector enzymes that transduce divergent signals from upstream receptor pathways and are responsible for catalyzing the conversion of ATP to cAMP. The ten AC isoforms are categorized into four main groups; the class III or calcium-inhibited family of ACs comprises AC5 and AC6. These enzymes are very closely related in structure and have a paucity of selective activators or inhibitors, making it difficult to distinguish them experimentally. AC5 and AC6 are highly expressed in the heart and vasculature, as well as the spinal cord and brain; AC6 is also abundant in the lungs, kidney, and liver. However, while AC5 and AC6 have similar expression patterns with some redundant functions, they have distinct physiological roles due to differing regulation and cAMP signaling compartmentation. AC5 is critical in cardiac and vascular function; AC6 is a key effector of vasodilatory pathways in vascular myocytes and is enriched in fetal/neonatal tissues. Expression of both AC5 and AC6 decreases in heart failure; however, AC5 disruption is cardio-protective, while overexpression of AC6 rescues cardiac function in cardiac injury. This is a comprehensive review of the complex regulation of AC5 and AC6 in the cardiovascular system, highlighting overexpression and knockout studies as well as transgenic models illuminating each enzyme and focusing on post-translational modifications that regulate their cellular localization and biological functions. We also describe pharmacological challenges in the design of isoform-selective activators or inhibitors for AC5 and AC6, which may be relevant to developing new therapeutic approaches for several cardiovascular diseases.